(untitled) (Indian Journal of Chemistry (IJC), 2025)
Leprosy is an infectious chronic disease and a neglected tropical disease induced by Mycobacterium leprae, and mainly affects the skin, peripheral nerves, upper respiratory mucosa and eyes. The prolonged physical deformities associated with leprosy get progressively worse with delayed diagnosis and increasing age. Desoxyfructoserotonin is a leprostatic agent, herein this paper we report its synthesis using 5-methoxy indole and the desired chiral centres was incorporated using naturally obtaing sugar moiety (D)-mannitol employing Vilsmeier- Haack reaction and Henry reactions. Keywords: Hanson’s disease, Desoxyfructoserotonin, Vilsmeier-Haack reaction and Henry reactions